Audit E-SPT Information System Using Cobit 4.1 Framework - Eka SETIAJATNIKA; Muhammad Ardi Nupi HASYIM; Heri NUGRAHA; Septafeta Petra Ramot SIMAMORA (International Journal of Environmental, Sustainability, and Social Science, 2020)
The purpose of this study is to determine the effect of knowledge sharing on teacher job satisfaction, to determine the effect of knowledge sharing on teacher performance, to determine the effect of teacher job satisfaction on teacher performance, to determine the effect of knowledge sharing on teacher performance mediated by teacher job satisfaction. The population in this study were 1156 teachers with the research sample involving 200 teachers. The research method used in this research is explanatory research, while the data analysis technique used is Structural Equation Modeling (SEM) with AMOS 23 and SPSS 21 software. The results show that (1) knowledge sharing has an effect on teacher job satisfaction. 2) knowledge sharing affects teacher performance, (3) job satisfaction affects teacher performance.